2009
DOI: 10.1074/jbc.m109.052969
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Neuronal Nuclei (NeuN) as Fox-3, a New Member of the Fox-1 Gene Family of Splicing Factors

Abstract: NeuN (neuronal nuclei) is a neuron-specific nuclear protein which is identified by immunoreactivity with a monoclonal antibody, anti-NeuN. Anti-NeuN has been used widely as a reliable tool to detect most postmitotic neuronal cell types in neuroscience, developmental biology, and stem cell research fields as well as diagnostic histopathology. To date, however, the identity of its antigen, NeuN itself, has been unknown. Here, we identify NeuN as the Fox-3 gene product by providing the following evidence: 1) Mass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
310
1
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 339 publications
(337 citation statements)
references
References 40 publications
23
310
1
3
Order By: Relevance
“…Although NeuN was not identified as a target of NPAS4 in previous studies (13,45), NeuN has been identified as a transcriptional factor, FOX-3, and appears to be a nervous system-specific nuclear regulatory molecule and a splicing regulator (46,47). In our study, a ChIP assay showed that Npas4 binds the promoter of NeuN in Neuro2a cells.…”
Section: Discussionmentioning
confidence: 73%
“…Although NeuN was not identified as a target of NPAS4 in previous studies (13,45), NeuN has been identified as a transcriptional factor, FOX-3, and appears to be a nervous system-specific nuclear regulatory molecule and a splicing regulator (46,47). In our study, a ChIP assay showed that Npas4 binds the promoter of NeuN in Neuro2a cells.…”
Section: Discussionmentioning
confidence: 73%
“…This monoclonal antibody recognizes a double band of 46-58 kDa in Western blots of mouse brain nuclear extracts (Mullen et al, 1992), which recently were shown to correspond to the splicing factor Fox-3 (Kim et al, 2009). In whole brain Western blots it additionally recognizes a band of 70 kDa, identified as synapsin I, but this crossreactivity disappears with paraformaldehyde fixation (Kim et al, 2009) and is not apparent in immunostained sections. Our immunostaining of neuronal nuclei and cell bodies in the spinal cord is identical to that reported previously by us and that reported in spinal cord atlases (Watson et al, 2009).…”
Section: Neun Antibodymentioning
confidence: 99%
“…This antibody may crossreact with other protein that labels axonal structures in mouse brain section if section is not well permeated with triton. On the gel, it gives rise to 2 bands at around 38 and 50kDa (Kim et al, 2009). …”
Section: Antibody Characterizationmentioning
confidence: 99%
“…The immunogen for this antibody is purified cell nuclei from mouse brain, but later has been shown to detects RNA spicing factor Fox-3 (Kim et al, 2009). In our hands, not all neuronal nuclei are labeled with this antibody in the brain.…”
Section: Antibody Characterizationmentioning
confidence: 99%